Profile of People With HIV-AIDS (PLWHA) During The Covid-19 Pandemic By Stress Levels - Indah Jayani; Susmiati; Satria Eureka (Journal of Nursing Science Update (JNSU), 2022)
The COVID-19 pandemic presents complex problems, especially in the health sector, especially for people with HIV-AIDS (PLWHA), who are one of the groups vulnerable to COVID-19 transmission. Psychological responses shown by PLWHA are anxiety and stress. Various factors allegedly affect stress in PLWHA. This study aimed to determine the factors influencing stress levels in PLWHA during the covid-19 pandemic. The research design is descriptive-analytic with a cross-sectional approach using primary data. The sample of 34 people living with HIV in the Kediri area was obtained by purposive sampling. Inclusion criteria were PLWHA aged 20-55 years and cooperative. Exclusion criteria included people living with HIV with advanced complications or severe opportunistic infections. The instrument measuring stress uses the Depression Anxiety Stress Scale 42 (DASS 42). Analysis of the Spearman rank correlation test data showed that there was no relationship between gender and age with stress levels (ρ-value = 0.428 > =0.05, -value = 0.131>α=0.05), and there was a relationship between education, knowledge , social support with stress levels in PLWHA in the Kediri area (ρ-value = 0.000 > =0.05, (r)=-600), -value = 0.000 < =0.05, (r)=-0.658 , p-value < d =0.05, (r)=-799). Respondents can actively increase knowledge related to COVID-19 through accountable information media and be open with families, communities, and health workers to get high support from families, communities and health workers as a priority for vulnerable groups in efforts to prevent COVID-19.